Design and Implementation of an Optimal PV Solar Generator in Tropical Zone - Andre Youmssi; Emmanuel Patrick Feudjio (Novel Perspectives of Engineering Research Vol. 2, 2021)
Many small enterprises, other organisms, and rural populations, primarily in developing countries, lack easy access to the grid, necessitating the use of decentralised electric sources, which are critical in some situations, particularly when supplying rural hospitals or pumping drinkable or irrigation water. Electric Solar Generators Technologies could possibly come to the rescue in a big way. This article focuses on the analysis of key factors for a PV Solar Generator design and implementation. In that regard, we conducted a study of the state of the art in the domain of Solar Electric Generators, which provided key parameters of each component of a safe, easy-to-maintain feeding solar system, and led us to the design, notably through the software PVSyst, of a domestic flat PV solar generator, as well as to the implementation and testing of a domestic flat PV solar generator. A PV panel’s generator equipped with batteries seems the most advantageous among the decentralised electricity production systems like generating units The designed schematics, tables, and curves of simulated and experimented electric quantities such as maximum delivered powers and efficiencies comprise the results. The article provided an example of a fully installed PV system that was instrumented for data logging.That system included a battery and an inverter to power real loads. The system design parameters included the size of the PV array, battery size, inverter power rating, and power delivered to the loads. The data logged has been used to evaluate the designed system and make assessments on how the design of the system could be enhanced so that systems of this type could serve the local needs most economically.